Los tipos de hábitat en Buenos Aires: poblamiento, estructura demográfica y condiciones residenciales - Marcos, Mariana; del Río, Juan Pablo (El Colegio de México A.C., 2022)
Habitat types are urban environments resulting from the settlement process of the city and the forms of production of the living space. The article aims to investigate the way in which habitat types are linked to the demographic profile, the characteristics of the housing stock and the metropolitan location market in Buenos Aires, based on recent census data. As a result, the housing conditions are described in the light of the genetic variants of the settlement process, and the contrasts, similarities, hierarchies and distances among urban environments are highlighted.